A Critical Evaluation of Smara Sādhanā Concepts in The Lontar Kama Tattwa for Strengthening Premarital Education - Gede Agus Siswadi; Lasiyo Lasiyo; Rr Siti Murtiningsih (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to critically evaluate the concept of Smara Sādhanā as presented in the Lontar Kama Tattwa and to examine its relevance in strengthening premarital education in Denpasar. The research addresses the growing phenomenon of premarital sexual practices and the shifting moral values reflected in the discourse of “sing beling sing nganten,” which indicate a process of desacralization of marriage and sexuality. Methodology: This research employs a qualitative approach with a critical–interpretative design. Primary data are derived from classical Balinese Hindu texts categorized under Kama Tattwa. Secondary data are collected from scholarly literature and relevant studies. Main Findings: The findings reveal that Smara Sādhanā conceptualizes sexuality as a sacred and conscious practice that integrates physical, psychological, and spiritual dimensions, grounded in dharma and realized within the institution of marriage. The study also finds that contemporary social phenomena, such as the normalization of premarital sex and gender bias, reflect a disconnection between traditional ethical teachings and modern practices. Novelty/Originality of this study: This study offers a novel contribution by bridging classical Hindu philosophical texts with contemporary educational and social issues. It reconstructs premarital education through the lens of Smara Sādhanā, positioning sexuality as a form of spiritual discipline rather than merely a biological or social act. Furthermore, this research introduces a culturally rooted and philosophically grounded framework that addresses both moral challenges and gender issues in modern Balinese society, thereby enriching the discourse on sexuality education within religious and cultural contexts.